2011
DOI: 10.4314/ajnt.v4i3.71029
|View full text |Cite
|
Sign up to set email alerts
|

Systemic Lupus Erythematosus with Severe Nephritis That Mimicked Henoch-Schoenlein Purpura

Abstract: Introduction: Systemic lupus erythematosus (SLE) belongs to a family of related autoimmune rheumatic disorders that are capable of affecting multiple organs, and they are all associated with a variety of autoantibodies. Henoch Schoenlein purpura (HSP) is a sort of systemic vasculitis that is not associated with auto-antibodies and can affect different organs including the kidneys.Case report: A 12 year-old girl presented with abdominal pain, low grade fever, swollen and tender feet and left hand, skin rash on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
7
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…In 2011, Al-Attrach et al . first reported a 12-year-old girl who presented with features of HSP and was later diagnosed to have SLE [6]. …”
mentioning
confidence: 99%
“…In 2011, Al-Attrach et al . first reported a 12-year-old girl who presented with features of HSP and was later diagnosed to have SLE [6]. …”
mentioning
confidence: 99%
“…Al attarch et al reported a 12 year old girl who presented with HSP with severe IgA nephropathy and responded to treatment but eventually developed lupus. The histopathology did not reveal a full house in the child on immunofluorescence [15]. Abdawani et al reported a 13 year old boy with HSP with nephritic range proteinuria and a full house picture on immunofluorescence which improved with aggressive treatment like our patient [16].…”
Section: Discussionmentioning
confidence: 50%
“…There are only four case-reports published in the medical literature in which the association between IgA vasculitis (HSP) and jSLE is present [1316]. The case described by Al-Attrach [14] is particularly interesting due to the similarity to our cases. The patient was a 12-year-old girl diagnosed with IgA vasculitis (HSP) based on skin, joint, abdominal, and renal affection, after 5 months on treatment with corticosteroids and mycophenolate mofetil, she attained withdrawal of medications.…”
Section: Discussionmentioning
confidence: 60%